Reconstruction of Nasal Defects With Dermal Skin Substitutes—A Retrospective Study of 36 Defects. Issue 4 (July 2019) - Moratin, Katharina; Koch, Philipp-Sebastian; Benecke, Johannes; Orouji, Azadeh; Bauer, Corinne; Faulhaber, Jörg; Koenen, Wolfgang; Felcht, Moritz
Objectives: It is uncertain whether dermal regeneration templates (DRTs) are helpful to reconstruct nasal defects. The aim of this study was to assess whether the aesthetic subunits determine the outcome. Methods: In this unicentric, retrospective study, the surgical procedures and outcomes of patients who received DRTs to reconstruct nasal defects were assessed and compared with the involved aesthetic subunits. Results: DRTs were used for reconstruction of 36 nasal defects in 35 patients with involvement of 76 aesthetic subunits: nasal sidewall (n = 21), nasal ala (n = 13), nasal tip/columella (n = 12, n = 1, respectively), nasal dorsum (n = 12), and extranasal aesthetic areas (n = 17). Fifty-eight nasal and 8 extranasal aesthetic subunits were reconstructed with DRTs, 10 subunits with a flap. Twenty-nine of 36 defects healed without any complications (80.5%). All reconstructed nasal tips/columella and the nasal dorsa healed without any complications. Region-specific complications were retraction of the ala rim (4/12; 33.3% of the patients with involvement of the nasal ala) and the formation of a fistula in the nasal sidewall (1/21; 4.8%). Region-specific complications of extranasal subunits were the development of an ectropium (2/3; 66.7% of the patients with involvement of the lower lid). Conclusions: DRTs can be helpful to reconstruct nasal defects. However, if the defect involves the aesthetic subunits nasal ala or the infraorbital region, different techniques should be preferred.